The Effectiveness of Mindfulness-Based Cognitive Behavior Therapy Group Counseling to Reduce Foreign Language Classroom Anxiety through Self-Efficacy in Grade IX Students of MTs PPMI Assalaam Sukoharjo - Romadhona, Nur Fitra; Eddy Wibowo, Mungin; Mulawarman, Mulawarman (Universitas Negeri Semarang, 2022)
Foreign language anxiety is considered as one of disrupting factor for students to perform well in English class. This study attempted to determine the effectiveness of mindfulness-based cognitive behavior therapy group counseling to reduce foreign language classroom anxiety through self-efficacy in students at PPMI Assalam Sukoharjo. There were 14 students divided into two groups of experimental group and control group with equal amount randomly. The students experimental group got 6 times treatment of mindfulness-based cognitive behavior therapy. In collecting their data, a questionnaire with a likert scale was used. Following the data collection, repeated measures ANOVA test and mediation analysis were carried out. Findings revealed that based on an interactional analysis, there found greater reduction of foreign language classroom anxiety in the experimental group (F(3,11) = 10.789, with sig (p) = 0.007 < 0, 05. This can also be seen in the results of the second hypothesis testing indicated by the calculated F value for the experimental group, namely 11.061 with sig (p) 0.007 <0.05. In other words, the mindfulness-based cognitive behavior therapy group counseling has proved effective in reducing foreign language classroom anxiety through self-efficacy in grade IX students at MTs PPMI Assalaam Sukoharjo. Hasil penelitian menegaskan analisis interaksi yang menjadi dasar dalam pembuktian hipotesis menunjukkan bahwa terdapat penurunan foreign language classroom anxiety yang terjadi pada kelompok eksperimen yang lebih besar daripada kelompok kontrol (F(3,11) = 10,789, dengan sig (p) = 0,007 < 0,05. Hal ini juga terlihat pada hasil pengujian hipotesis kedua yang ditunjukkan dengan nilai F hitung untuk kelompok perlakuan sebesar 11,061 dengan sig (p) 0,007 < 0,05. Dengan kata lain, konseling kelompok mindfulness based cognitive behavior therapy terbukti efektif untuk mereduksi foreign language classroom anxiety melalui self-efficacy pada siswa kelas IX MTs PPMI Assalaam Sukoharjo.